Creating psychological connections between intervention recipients: development and focus group evaluation of a group singing session for people with aphasia. Issue 2 (23rd February 2016) - Tarrant, Mark; Warmoth, Krystal; Code, Chris; Dean, Sarah; Goodwin, Victoria A; Stein, Ken; Sugavanam, Thavapriya
Abstract : Objectives: The study sought to identify key design features that could be used to create a new framework for group-based health interventions. We designed and tested the first session of a group intervention for stroke survivors with aphasia which was aimed at nurturing new psychological connections between group members. Setting: The intervention session, a participant focus group and interviews with intervention facilitators were held in a local community music centre in the South West of England. Participants: A convenience sample of 10 community-dwelling people with poststroke aphasia participated in the session. Severity of aphasia was not considered for inclusion. Intervention: Participants took part in a 90-min group singing session which involved singing songs from a specially prepared song book. Musical accompaniment was provided by the facilitators. Primary and secondary outcome measures: Participants and group facilitators reported their experiences of participating in the session, with a focus on activities within the session related to the intervention aims. Researcher observations of the session were also made. Results: Two themes emerged from the analysis, concerning experiences of the session ('developing a sense of group belonging') and perceptions of its design and delivery ('creating the conditions for engagement'). Participants described an emerging sense of shared social identity as a member of the intervention group and identified fixed (eg, group size, session breaks) and flexible (eg, facilitator responsiveness) features of the session which contributed to this emergence. Facilitator interviews and researcher observations corroborated and expanded participant reports. Conclusions: Engagement with health intervention content may be enhanced in group settings when intervention participants begin to establish positive and meaningful psychological connections with other group members. Understanding and actively nurturing these connections should be a core feature of a general framework for the design and delivery of group interventions.